Brain histology. Issue 5 (16th September 2008) - Jeans, A; Esiri, M
Abstract : In this article we summarise nervous system histology in health and disease and acquaint the reader with developments in the staining techniques that are in current use, particularly immunostains. Although clinicians do not need to know the details of stain appearances, some familiarity with these aspects of neuropathology is invaluable in interpreting the reports they receive from the laboratory, as well as reminding them of the amazing beauty of the central nervous system's microscopic structure.